Give it to us straight (most of the time): Top managers' use of concrete language and its effect on investor reactions - Pan, Lingling; McNamara, Gerry; Lee, Jennifer J.; Haleblian, Jerayr (John); Devers, Cynthia E. (Strategic Management Journal, 2018)
[Research summary: Building on the communications and linguistics literatures, we explore the language attributes managers use in interactions with investors and the subsequent reactions of investors. Specifically, we hypothesize that top managers' use of concrete language attributes in communication with investors broadly associates with positive investor reactions. We further posit that this relationship will be moderated by the level of firm risk. Our results support our hypotheses and, thus, offer important insights to the impression management literature. First, subtle elements of managerial communication can have significant impression management consequences. More specifically, language concreteness is a key language attribute that generally induces positive investor responses. Finally, the effectiveness of language concreteness is conditional on the informational environment of the firm. Managerial summary: How can managers communicate in a way that presents the firm more positively or reduces the negativity associated with perceived firm risks? Our findings indicate that choosing appropriate persuasive language features in interactions with investors can help a firm manage its impressions. Specifically, we find that top managers' use of concrete language that provides details and specific information in communication with investors, in general, garners positive investor reactions. Further, the effectiveness of top managers' use of concrete language depends on investor concerns. More specifically, we find that when a firm is seen as having a riskier profile, using concrete language helps induce a more positive investor response; while when a firm is seen as low risk, using abstract language may be more beneficial.]